PPCPs abatement using TiO2-based catalysts by photocatalytic oxidation and ozonation: the effect of nitrogen and cerium loads on the degradation performance and toxicity impact - Domingues, Eva (2023)
Pharmaceutical and personal care products (PPCPs) have been consumed in great extension and most of these are found in water bodies, owing to the inefficiency of conventional wastewater treatments. To face against these recalcitrant contaminants, advanced oxidation processes such as photocatalysis and ozonation have been studied. Moreover, the combination of these technologies can improve the degradation of PPCPs, reducing the ozone consumption and the effluent toxicity with the presence of photocatalysts. In particular, this study aimed to evaluate the effects of different N and Ce loads in co-doping TiO2 catalysts on the efficiency of photocatalytic oxidation and photocatalytic ozonation for PPCPs abatement, as well as on the resultant toxicity to aquatic species. Different radiation sources (UVA and solar radiation) were considered for the photocatalytic oxidation. A mixture of 5 PPCPs: paracetamol, sulfamethoxazole, carbamazepine, methylparaben and propylparaben was used as a model synthetic effluent. Photocatalysis showed a low efficiency on the PPCPs removal (<20 %), which was not affected by the radiation source. In general, the tested catalysts showed no or low added-value for reducing the toxicity of the synthetic effluent. Concerning photocatalytic ozonation, the lowest N amount (2.5 % w/w) promoted the best results for PPCPs removal, achieving values up to 100 % with significant reduction of ozone dose compared to photolytic ozonation. In general, photocatalytic ozonation showed better ecotoxicological performance than single photocatalysis. Compared to single photolytic ozonation, a benefitial effect was observed for two aquatic species, using a specific catalyst. This catalyst, prepared by doping TiO2 with 2.5 % w/w N and 1.2 % w/w Ce, showed to be the most promisong one, with potential to be used in photocatalytic ozonation. Hence, this work highlights the potential role of N and Ce co-doped TiO2-based catalysts in photocatalytic ozonation for wastewater treatment.